Effect of V-, Cr-, and Mn-doped rutile TiO2 on dielectric properties in a nanocapacitor: A theoretical approach - Hossein Movahedi Aliabad; Seyedeh Bahareh Islami rad; Seyedeh Zahra Islami rad (AIP Advances)
One of the main factors affecting the dielectric properties of materials in nanocapacitors is the presence of dopants in the material. In this study, the electronic structure and dielectric properties of rutile titanium dioxide (TiO2) doped with vanadium (V), chromium (Cr), and manganese (Mn) dopants (X dopant) are investigated based on density functional theory. The simulation results indicate that the application of dopants reduces the charge distribution around Ti and O atoms, leading to a weakening of the Ti–O bond. Density of states and partial density of States show that the electron contribution of X 3d orbitals increases and the electron contribution of O 2p and Ti 3d orbitals decreases. The bandgap of V-, Cr-, and Mn-doped rutile decreases to 1.608, 0.84, and 0.21 eV, respectively, due to the formation of new impurity levels and enhanced conductivity. In addition, the dielectric constants (k) for V-, Cr-, and Mn-doped rutile in certain directions are measured as 47.7, 63.06, and 89.43, respectively. The results show that doping with metal elements positively impacts the aforementioned properties and can be considered a reasonable electronic application technique. Although the dielectric constant has improved at least fourfold compared to undoped rutile, Cr and Mn dopants are unsuitable for semiconductor dielectric applications due to their low bandgaps. Therefore, V-dopant is a suitable dopant in comparison with the electronic properties of other dopants for dielectric applications.